A Case of Simultaneous, Biopsy-Proven, Classic, ANCA-Positive Wegener's Granulomatosis and Anti-GBM Disease, but without Detectible Circulating Anti-GBM Antibodies - Aleksandra Gmurczyk; Shubhada N. Ahya; Robert Goldschmidt; George Kim; L. Tammy Ho; Kevin Nash (The Scientific World Journal)
Wegener's granulomatosis (WG) is a systemic, necrotizing, granulomatous vasculitis of unknown etiology. Approximately 75% of cases present as classic WG with both pulmonary and renal involvement, while the remaining 25% of patients present with a limited form with either predominantly upper or lower respiratory tract symptoms. Ninety percent of WG patients have circulating anti–neutrophil cytoplasmic antibodies (ANCA), and approximately 10% have both circulating ANCA antibodies and concomitant anti–glomerular basement membrane (anti-GBM) disease on renal biopsy. Virtually all of these patients also have circulating anti-GBM antibodies. While it has been reported that some patients with ANCA vasculitis have circulating anti-GBM antibodies, and patients with anti-GBM disease may have positive ANCA, review of the literature does not demonstrate other cases of biopsy-proven, simultaneous, ANCA-associated vasculitis and anti-GBM disease. We report a case of simultaneous, biopsy-proven, classic, ANCA-positive WG and anti-GBM disease, but without detectible circulating anti-GBM antibodies. We present findings characteristic of both WG and linear IgG deposition along the GBM suggesting concurrent anti-GBM disease, in the absence of detectable circulating anti-GBM antibodies. Possible theories to explain the absence of these antibodies are discussed.